Bibliographic instruction and critical thinking - Ballesteros, Kathleen Lourdes M.; Yang, Jackson V.; Gatmaitan-Borjal, Wilhelmina (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
With the increasing bulk of information produced as well as with the increasing reliance on global network, there is a need to educate more information literate students. The current situation is providing an opportunity for librarians to play a major role in providing the student the needed skills in dealing with the fast changing environment of information and information technology. It is one of the responsibilities of librarians to educate independent information seekers.
The goal in libraries in this situation is for librarians to help the users reach a level of critical thinking or reflective judgment so that the users will be able to make good decisions on which resources to search. As such, they would be able to identify and locate appropriate information within the sources, integrate the information into their understanding of the topics then produce a written output. This research has been conceptualized to determine whether Bibliographic Instruction can address such need for the development of the level of critical thinking or reflective judgement called for today.
The study compared the critical thinking of freshmen students of the Divine Word College of Laoag enrolled in English I classed during the first semester of AY 2001-2002. One class was assigned as the treatment group, to which the Bibliographic Instruction was administered throughout the semester for one hour each week for 18 weeks, aside from attending the English I class. The other class was assigned as the control group where they look the same English I course. A pretest and posttest was administered to both classes to determine the level of critical thinking of the students before and after the treatment. This also determined the gains in the critical thinking of the students.
The study found that there is no significant difference in the gains in the critical thinking of the students exposed to Bibliographic Instruction from those who were not. In conclusion, Bibliographic Instruction did not develop critical thinking among the students who were exposed to such.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Divine Word College of Laoag; Library orientation -- Philippines -- Laoag; Library orientation for college students -- Philippines -- Laoag; Information services -- Philippines -- Laoag -- User education; Critical thinking -- Philippines -- Laoag